2022
DOI: 10.1186/s13018-022-03149-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative position and protection of radial nerve by B-ultrasound combined with MIPPO for treatment of middle-inferior humerus fractures

Abstract: Background and purpose Open reduction and internal fixation through the posterior approach are standard methods for treating middle-inferior humerus fractures. Given the limited operative field and difficulty in locating the radial nerve, the minimally invasive percutaneous plate osteosynthesis (MIPPO) technique via the posterior approach to treat middle-inferior humerus fractures has rarely been reported. This study aims to evaluate the clinical effect of the preoperative study of the radial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Iatrogenic radial nerve injury has been reported in 2.7%-20% of humeral shaft fractures, and is mainly associated with insufficient exposure and excessive traction [ 24 ]. In our recent study, we found that preoperative precise positioning using ultrasound and intraoperative pull methods reduced iatrogenic radial nerve injury, thereby increasing the efficiency of MIPO [ 25 ]. Additionally, the radial nerve passes through the posterior aspect to anterolateral at an average of 14 cm from the humeral lateral epicondyle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic radial nerve injury has been reported in 2.7%-20% of humeral shaft fractures, and is mainly associated with insufficient exposure and excessive traction [ 24 ]. In our recent study, we found that preoperative precise positioning using ultrasound and intraoperative pull methods reduced iatrogenic radial nerve injury, thereby increasing the efficiency of MIPO [ 25 ]. Additionally, the radial nerve passes through the posterior aspect to anterolateral at an average of 14 cm from the humeral lateral epicondyle [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to its xed position in the radial sulcus and direct contact with the humeral periosteum after passage through the medial intermuscular septum. Our recent study inclined that preoperative precise positioning by B-ultrasound and intraoperative pull method reduced iatrogenic injury of the radial nerve, thereby increasing the e ciency of MIPO [25]. However, the radial nerve passes through the posterior aspect to anterolateral at an average of 14 cm from the humeral lateral epicondyle [26].…”
Section: Discussionmentioning
confidence: 99%